Bird Species Inventory in Tlogoguwo Village, Purworejo - Afidah, Pepy Noer; Rosid, Vidia Fadilah; Prawestri, Esy; Fitriana, Fitriana (Proceeding International Conference on Religion, Science and Education, 2024)
Tlogoguwo village is located in the Menoreh karst mountains, which administratively belongs to Kaligesing Sub-district, Puworejo District. Tlogoguwo is located at an altitude of 700 meters above sea level, and has riverine, agroforestry, and secondary forest habitats. These habitats provide varied vegetation cover that supports bird survival such as foraging, nesting, sheltering, and resting.. Unfortunately, information on bird species data in Tlogoguwo Village is minimal, therefore this inventory activity is important to update bird species data in Tlogoguwo Village. This study aims to obtain data on bird species found in Tlogoguwo Village and determine their conservation status. This data can be used as a reference base for further bird research or as a basic foundation in developing biodiversity protection strategies. Bird species inventory research in Tlogoguwo Village was carried out on March 19-27, 2022 every Saturday and Sunday. Each day the data collection was divided into 2 sessions, namely, session 1 (07.00-10.00 WIB) and session 2 (14.30-17.30 WIB). The method used in this study is a combination of the Cruising method and the Encounter Rates method. The data obtained were analyzed using the relative abundance index and tabulated in tabular form. The results showed that there were 40 bird species from 23 families spread throughout the observation area. The abundance value of birds was categorized into 6 species “frequent” and 34 species “uncommon”. Protected bird conservation status by P 106 2018, there were 3 bird species. The conservation status by IUCN in this study is classified into 3 categories, that endangered (EN), vulnerable (VU) and least concern (LC). The Status of international trade according to CITES indicates 3 species are included in Appendix II.